IMPLEMENTASI KEBIJAKAN PENGELOLAAN UNIT USAHA BADAN USAHA MILIK DESA DI DESA LEREP KECAMATAN UNGARAN BARAT KABUPATEN SEMARANG - Ayuni, Chyntya Iga; Hidayat, Zainal (Journal of Public Policy and Management Review, 2019)
Minister of Villages, Disadvantaged Regions, and Transmigration Regulation No. 5 of 2015 on The Establishment, Arrangement and Management, and Dismissal of Villageowned Enterprise followed up in regional area by Regulation Regional Regulation of Semarang Regency No. 17 of 2016 on The Establishment and The Management of Village-owned Enterprise and Shared Village-owned Enterprise regulated about the management of business units of village-owned enterprise. Desa Lerep is a village in Kabupaten Semarang that has been implementing village-owned enterprise for almost two years. The purpose of this research is to find out about how the management policy of business units being implemented in Desa Lerep, as well as the factor affecting of the implementation. This research used a descriptive method-qualitative approach. The result showed that village-owned enterprise in Desa Lerep named BUMDes Gerbang Lentera has seven business units: Public Service Unit, Small Industrial Unit, Rental Unit, General Trading Unit, Tourism Unit, Microfinance Institution Unit, and Fisheries and Livestock Unit. Each units did certain business in order to achive their respective goals. Among the seven units, General Trading Unit and Tourism Unit are the ones which show the most business perfomance more than the other. Whilst Microfinance Institution Unit show the least business perfomance of all other units. Affecting factors of the implementation are villagers participation, coordination, collaboration, limited funds, and the staffs activeness. The writer suggests to do a training on processing house waste into compost, using the authentic culinary of Desa Lerep as a catering menu, selling the local products of Desa Lerep on online sites, optimizing the saving and investment of Desa Lerep villagers, and strengthen the work ethic of BUMDes Gerbang Lentera’s staffs.